M6 Outcomes of pulmonary mycobacterium abscessus infection. (12th November 2019) - Flight, WG; Hough, NE; Chapman, SJ
Abstract : Background: Treatment of Mycobacterium abscessus pulmonary disease is challenging with frequent side effects. There is little published data from UK settings to guide treatment decisions in M. abscessus infection. Methods: Patients at our centre with ³1 respiratory sample positive for M. abscessus from 2014 to 2019 were identified. Health records were reviewed retrospectively to determine factors associated with M. abscessus infection and clinical outcomes. Clearance of M. abscessus was defined as ³6 negative samples over ³12 months off treatment. Results: Thirty-seven patients were identified of whom 24 (64.9%) had cystic fibrosis (CF), 10 (27.0%) bronchiectasis, 2 (5.4%) COPD and 1 (2.7%) asthma. Median age at first M. abscessus isolate was 21 years (range 13–56) and 70 years (56–89) among CF and non-CF patients respectively. ATS/IDSA criteria for NTM-pulmonary disease were met in 21/37 (56.8%) of cases. Six patients (16.2%) had a single isolate only. Initial isolates were smear-positive in 21/37 (56.8%). Susceptibility testing for Amikacin revealed 66.7% of initial isolates were sensitive, 25.0% intermediate and 8.3% resistant. Equivalent values for Clarithromycin were 20.0%, 12.0% and 68%. Thirteen patients (35.1%) isolated ³1 other NTM ( M. avium complex n=10, M. fortuitum n=2, M. gordonae n=2 and M. triplex n=1). Eighteen patients with CF (75%) had features of Aspergillus lung disease (ABPA n=9, Aspergillus sensitisation n=5 and Aspergillus bronchitis n=4) compared with 3 (23.1%) among non-CF patients. Induction therapy was given to 22/37 (59.5%) patients (including 18/24 (75%) with CF and 4/13 (30.8%) without CF). Median duration of induction therapy was 6 weeks (range 3–12). Maintenance antibiotic therapy was prescribed to 17/22 (77.3%) of treated patients. Culture conversion was seen in 16/24 (66.7%) of CF patients compared with 4/13 (30.8%) of non-CF patients. Among CF patients with culture conversion, 11/16 (68.8%) had received treatment while all four of the non-CF patients who received treatment failed to convert. Clearance of M. abscessus was confirmed in 12/37 patients (32.4%) of whom 6 had received treatment. Conclusion: Most patients with M. abscessus isolates met ATS/IDSA criteria for NTM-pulmonary disease. Culture conversion was more common in patients with CF but often occurred spontaneously in both groups.